Pengenalan Digital Marketing Pada Usaha Keripik Singkong Dewi Sri di Desa Bukit Peninjauan 1 - Afriani, Sulisti; Yanti, Rina Trisna; Noviantoby, Noviantoby; Maulana, Taufik; Berlianza, Dhendy (Universitas Dehasen Bengkulu, 2022)
Cassava chips are a type of food that is familiar to us. The delicious taste makes these chips a product that is liked by all levels of society. UMKM of cassava chips Dewi Sri is one of the UMKM that produces and sells this cassavabased product. The method of implementing the activity consists of a presentation method by providing an explanation through direct delivery and a question and answer method or discussion. The flow of the stages of this community service activity consists of the preparation stage, the implementation stage and the evaluation stage. UMKM Cassava Chips Dewi Sri provides a variety of flavors, namely spicy, salty and sweet corn flavors. Cassava Chips produced by the Dewi Sri Cassava Chips UMKM average around 240 kg/day. This production capacity is still limited because some production equipment is still semi manual. The use of digital technologybased marketing can be a new breakthrough knowledge for Dewi Sri Cassava Chips UMKM to develop their marketing strategies through social media and marketplaces. The result of this Community Service activity is that Dewi Sri's Cassava Chips UMKM are increasingly understanding about digital marketing and are able to own and manage social media and marketplaces as promotional tools.